Untangling the Roles of Anti-Apoptosis in Regulating Programmed Cell Death using Humanized Yeast Cells - Clapp, Caitlin; Portt, Liam; Khoury, Chamel; Sheibani, Sara; Eid, Rawan; Greenwood, Matthew; Vali, Hojatollah; Mandato, Craig; Greenwood, Michael (Frontiers in Oncology, 2012)
Genetically programmed cell death (PCD) mechanisms, including apoptosis, are important for the survival of metazoans since it allows, among things, the removal of damaged cells that interfere with normal function. Cell death due to PCD is observed in normal processes such as aging and in a number of pathophysiologies including hypoxia (common causes of heart attacks and strokes) and subsequent tissue reperfusion. Conversely, the loss of normal apoptotic responses is associated with the development of tumours. So far, limited success in preventing unwanted PCD has been reported with current therapeutic approaches despite the fact that inhibitors of key apoptotic inducers such as caspases have been developed. Alternative approaches have focused on mimicking anti-apoptotic processes observed in cells displaying increased resistance to apoptotic stimuli. Hormesis and pre-conditioning are commonly observed cellular strategies where sublethal levels of pro-apoptotic stimuli lead to increased resistance to higher or lethal levels of stress. Increased expression of anti-apoptotic sequences is a common mechanism mediating these protective effects. The relevance of the latter observation is exemplified by the observation that transgenic mice overexpressing anti-apoptotic genes show significant reductions in tissue damage following ischemia. Thus strategies aimed at increasing the levels of anti-apoptotic proteins, using gene therapy or cell penetrating recombinant proteins are being evaluated as novel therapeutics to decrease cell death following acute periods of cell death inducing stress. In spite of its functional and therapeutic importance, more is known regarding the processes involved in apoptosis than anti-apoptosis. The genetically tractable yeast Saccharomyces cerevisiae has emerged as an exceptional model to study multiple aspects of PCD including the mitochondrial mediated apoptosis observed in metazoans. To increase our knowledge of the process of anti-apoptosis, we screened a human heart cDNA expression library in yeast cells undergoing PCD due to the conditional expression of a mammalian pro-apoptotic Bax cDNA. Analysis of the multiple Bax suppressors identified revealed several previously known as well as a large number of clones representing potential novel anti-apoptotic sequences. Here we will discuss the nature and function of the anti-apoptotic sequences as well as the fact that screens such as these provide greater insight into the processes of anti-apoptosis as well as serving to further uncover the functional similarities between yeast and human PCD.